FLAIR hyperintense cortical lesions in myelin oligodendrocyte glycoprotein-associated encephalitis with seizures in children: a retrospective single-center case series - Liu, Kang; Wang, Weixiu; Jin, Mei; Chen, Fang; Wang, Wei; Liu, Xiaohan; Sun, Suzhen (Frontiers in Immunology, 2025)
Background and purposeIn recent years, the number of case reports concerning fluid-attenuated inversion recovery (FLAIR) hyperintense cortical lesions in myelin oligodendrocyte glycoprotein (MOG) -associated encephalitis with seizures (FLAMES) has been gradually increasing. However, within the pediatric demographic, there remains a lack of related serial reports. This study was designed to characterize the clinical features and prognosis of FLAMES in pediatric patients.MethodsWe reviewed the medical records of children diagnosed with FLAMES from January 2019 to July 2024 and retrospectively analyzed their clinical manifestations, brain magnetic resonance imaging (MRI) findings, laboratory results, treatments, and outcomes.ResultsAmong the 123 children diagnosed with MOG antibody-associated diseases (MOGAD), 9 (7.3%) met the inclusion criteria for FLAMES. The median onset age was 9 years (range: 8-14), and the male-to-female ratio was 5:4. The most common clinical symptoms included seizures (9/9, with 6 experiencing focal seizures), altered mental status (6/9), headache (5/9), fever (4/9), and focal neurological deficits (3/9). Furthermore, three patients presented with status epilepticus, two with cranial nerve involvement (central facial paralysis and lingual paralysis), and two with Todd’s palsy. Seven patients had cerebrospinal fluid (CSF) pleocytosis (median count: 58/µL, range: 12-143/µL); two had elevated CSF pressure (range: 240–280 mmH2O); and one had mildly elevated CSF protein levels (0.46 g/L). All patients had normal CSF glucose levels. Abnormal electroencephalogram (EEG) findings were detected in seven patients: epileptic seizures (3/7), interictal discharges (6/7), and slow background activity (3/7). Unilateral cortical hyperintense lesions were observed in all nine cases on FLAIR imaging of brain MRI, affecting the frontal (8/9), parietal (3/9), temporal (2/9), and occipital (1/9) lobes. Five patients exhibited distinct linear enhancement of the corresponding cerebral sulci and/or meninges on gadolinium-enhanced brain MRI. All patients received immunotherapy, and six were administered anti-seizure medicines (ASMs). Each child achieved a satisfactory outcome and remained relapse-free at the final follow-up.ConclusionFLAMES exhibit an age-dependent pattern. Epileptic seizures are the most common clinical symptom, with focal seizures being the predominant type. FLAIR-hyperintense cortical lesions typically present unilaterally, predominantly affecting the frontal lobes. Enhancement of the corresponding cerebral sulci and/or meninges may be a distinctive feature in children. For children with epilepsy, in the presence of recurrent seizures without identifiable triggers, especially when cortical lesions are detected in cranial MRI, consideration should be given to the possibility of FLAMES.